APLIKASI MODEL KERJA KELOMPOK DALAM PENINGKATAN AKTIVITAS BELAJAR SISWA PADA PEMBELAJARAN IPA DI KELAS V SDN 35 PINCURAN VII - TUTI VERNI (JURNAL MANAJEMEN PENDIDIKAN, 2019)
This study aims to improve student learning activities in science subjects through the Application of the Group Work Model SDN 35 Pincuran VII, Tanah Datar District. This research belongs to CAR that takes place in two cycles each cycle consisting of two meetings. Besides that, each meeting consists of four stages, from planning, implementation, observation and reflection. The action was carried out in class V where students consisted of 25 people. Researchers in the study are assisted by an observer, who is the observer. The research data were analyzed with a percentage formula that describes the data as they are. The results of the study include: Learning Science in class V SDN 35 SDN Pincuran VII using the Use of Group Work Models Based on the results of classroom action research that has been carried out, the conclusion is that 1) The highest learning activity of students in the first and second cycles of the indicators answering questions and Concludes. 2) The lowest student learning activities in the first and second cycles are in the indicators of asking and collaborating activities. 3) Student activities in Mathematics learning from the first to the second cycle have increased through group work models in Class V SDN 35 Pincuran VII.